FAKTOR-FAKTOR YANG MENENTUKAN KEKUATAN GENGGAMAN TANGAN PADA PASIEN LANJUT USIA DI PANTI WREDHA TANGTU DAN POLIKLINIK GERIATRI RSUP SANGLAH - DENPASAR - Putrawan, IB Putu; Kuswardhani, RA Tuty (journal of internal medicine, 2012)
Handgrip strength is necessary for performing activities of daily living, which, in turn, are required to maintain functional activity. The purpose of this study was to determine anthropometric and personal factors that affect handgrip strength in groups of nursing home and out patients of Sanglah Teaching Hospital Denpasar-Bali. Body weight and height, Waist Circumference (WC), Mid-Upper-Arm Circumference (MUAC) and triceps skinfold, scapula skinfold and supra iliaca skinfold were obtained using standard techniques. Body height was estimated from kneeheight. Handgrip was measured using a mechanical handgrip dynamometer. A total of 38 male and 53 female aged 60 ? 82 years participated in the study. Both groups were statistically similar regarding all factors studied. Bivariate analyses showed that handgrip strength was associated with sex, age, WC, hemoglobin, albumin and body mass index in both of groups. Multiple linear regression analysis identified sex and WC (r = 0.39; p = 0.00), sex and age (r = 0.71; p = 0.00), as independent determinants of handgrip strength in both of groups. We conclude that women have a smaller handgrip strength than men. In addition, handgrip strength decreases with increasing age and decreasing WC.
Keywords: handgrip strength, anthropometric, age